Social Development of Organization: Problems and Prospects of Management - Tovma, N. (Farabi Journal of Social Sciences, 2016)
In article the concept is considered and factors of social development are defined. The principles of state regulation are allocated and stages of social development are defined, the technique of a rating assessment of social development is offered. The structure of the collective agreement is recommended. The bill on social development of organizations is considered. Models of social management are improved. Standards of social development of organizations are offered.